Well-being differences and changes in people with somatic and psychiatric disorders or multimorbidities: modelling COVID-19 as a global natural experiment of stress vulnerability - Till J Adam; Trevor Thompson; Fabiola H Peroz; Jan P Heisig; Paul Gellert; Enrique Alonso-Perez; Lara Bister; Lau Caspar Thygesen; Philippe Conus; Roland von Känel; Soraya Seedat; Denisa Manková; et al. (BMJ Mental Health, 2026)
Background Somatic and psychiatric illnesses and multimorbidities increase stress-vulnerability and decrease well-being. Objective We aimed to identify high-risk disorder profiles for lower well-being and well-being decline under stress, modelling COVID-19 as a natural experiment. Methods The global Collaborative Outcomes Study on Health and Functioning during Infection Times survey assessed the World Health Organization-Five Well-being Index (WHO-5) (0–100) retrospectively pre-pandemic and intra-pandemically. Mixed-effects models, controlling for demographic/pandemic-related covariates, examined coprimary outcomes: total pre-pandemic WHO-5 and pre-to-intra-pandemic change (estimating β); pre-pandemic WHO-5